Accounting for low solar resource days to size 100% solar microgrids power systems in Africa. (February 2019) - Plain, N.; Hingray, B.; Mathy, S.
Abstract: In many regions worldwide, the electrification of rural areas is expected to be partly achieved through micro power grids. Compliance with the COP21 conference requires that such systems mainly build on renewable energy sources. To deliver a high power and quality service may be difficult to be achieved, especially when micro-grids are based on variable renewable sources. We here explore the multiscale temporal variability of the local solar resource in Africa and its implication for the development of 100% solar systems. Using high resolution satellite data of global horizontal irradiance (GHI) for a 21-year period (1995–2015), we characterize the seasonality and temporal variability of the local resource. We focus on its low percentile values which give a first guess on the size of the solar panels surface required for the micro-grid to achieve a given quality service. We assess the characteristics and especially persistence of the low resource situations, for which the local demand would not be satisfied. We finally assess how the ability of electricity consumers for some day-to-day flexibility (e.g. via the postponement of part of one day as demand to the next), would help to achieve the design level of service quality with a smaller microgrid system. Graphical abstract: Highlights: 1.1 billion people lack access to electricity in the world, 80% live in rural areas. 100% solar microgrids (MG) are expected to provide electricity access in remote African areas. The power service quality will depend on the seasonal and daily variability of solar radiation. Using low percentile GHI values to design MG could help achieving a given power service quality. Design should account for some clustering of low resource days in specific seasons or time sequences.